2012
DOI: 10.1017/s1368980012000031
|View full text |Cite
|
Sign up to set email alerts
|

Fruit juice consumption is associated with improved nutrient adequacy in children and adolescents: the National Health and Nutrition Examination Survey (NHANES) 2003–2006

Abstract: Objective: To examine the contribution of 100 % fruit juice (FJ) consumption to dietary adequacy of shortfall nutrients by children and adolescents. Design: Cross-sectional. Setting: Secondary analysis of data from the 2003-2006 National Health and Nutrition Examination Survey (NHANES). Subjects: Children and adolescents aged 2-18 years (n 7250). Usual intake, determined from two 24 h dietary recalls, was calculated using the National Cancer Institute method. The population was dichotomized into consumers or n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
1
39
1
1
Order By: Relevance
“…A modeling study, commissioned by the 2005 Dietary Guidelines Advisory Committee [54] suggested that dietary fiber was lower when whole fruit was removed from the diet, which led to the recommendation that intake of no more than one-third of fruit servings should come from 100% FJ and two-thirds should come from whole fruit. However, this study and others [1-4,52] have shown that either consumers of 100% FJ had higher intakes of dietary fiber than non-consumers or there was no difference in fiber consumption between the groups. Since 100% FJ is low in dietary fiber, it suggests that other higher fiber foods, including whole fruit, are consumed by consumers of 100% FJ; this was shown not only in this study of 100% OJ consumers, but has been shown in other studies as well [1,2,52].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…A modeling study, commissioned by the 2005 Dietary Guidelines Advisory Committee [54] suggested that dietary fiber was lower when whole fruit was removed from the diet, which led to the recommendation that intake of no more than one-third of fruit servings should come from 100% FJ and two-thirds should come from whole fruit. However, this study and others [1-4,52] have shown that either consumers of 100% FJ had higher intakes of dietary fiber than non-consumers or there was no difference in fiber consumption between the groups. Since 100% FJ is low in dietary fiber, it suggests that other higher fiber foods, including whole fruit, are consumed by consumers of 100% FJ; this was shown not only in this study of 100% OJ consumers, but has been shown in other studies as well [1,2,52].…”
Section: Discussioncontrasting
confidence: 74%
“…Consumption of 100% fruit juice (FJ) has been associated with higher intakes of key nutrients, including vitamins C and B-6, folate, thiamin, magnesium, and potassium, as well as better diet quality, and increased intake of total and whole fruit consumption in children [1-4] and adults [3] as compared to those that do not consume 100% FJ. There have been concerns about overweight/obesity in consumers of 100% FJ, especially children [5-7].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the widespread attention from both scientific and public forums on the high sugar content of FJ may have influenced South African consumer perceptions (Basu et al, 2013;Boseley, 2016;Boulton et al, 2016;Greenwood et al, 2014;Saner, 2014;Wojcicki & Heyman, 2012). The press may have diminished the role of FJ as part of a healthy balanced diet quality, nutrient intake, and other health benefits, which is of vital importance in a developing country, since the consumption of FJ products is associated with a greater likelihood of meeting deficit vitamins and nutrients recommendations (Nicklas et al, 2015;O'Neil et al, 2011O'Neil et al, , 2012Rampersaud, 2015). However, this leads to the question if the proposed sugar tax is necessary, since a majority of consumers agree that FJ products are high in sugar content, and have either made an informed decision to continue (or not) to consume FJ products owing to the widespread FJ/sugar content discourse.…”
Section: Discussionmentioning
confidence: 99%
“…However, 100% FJ has recently become the focus of discussion owing to the naturally occurring sugar (fructose) contained in fruit. Discourse frequently focuses exclusively on the sugar content and ignores the potential health benefits and nutritional value, which relate to the consumption of FJ products (Nicklas et al, 2015;O'Neil et al, 2011O'Neil et al, , 2012Wojcicki & Heyman, 2012). Boseley (2016) reveals that FJ contains unacceptable high levels of sugar (sometimes more than soft drinks), but was marketed directly to children and parents using colorful packaging and health-related taglines.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation